Мифы, легенды и сказки удмуртского народа - Кралина Надежда Петровна (Удмуртия, 2019)
Экземпляры: СБ (20200923) / Инвентарный номер: 60089 / Цена: 480.00 / Сис.шифр: 82.3(2Рос.Удм) / Авт.знак: М 68 / ГРНТИ: 17.71.91 / ББК: 82.3(2Рос.Удм)